Uncanny valley eaudiobook A memoir. - Wiener, Anna (Macmillan Audio, 2020)
A NEW YORK TIMES BESTSELLER "Narrator Suehyla El-Attar has a strong voice for this memoir of a woman's journey into the mostly male world of tech start-ups in Silicon Valley. She is energetic, funny, and swift while telling the story of Anna Wiener's acculturation from book publishing in Manhattan to the dot-com boom in San Francisco." — AudioFile Magazine A New York Times Book Review Editors' Choice and a January 2020 IndieNext Pick. An Amazon Best Book of January. One of Vogue 's 22 Books to Read This Winter, The Washington Post 's 10 Books to Read in January, ELLE's 12 Best Books to Read in 2020, The New York Times 's 12 Books to Read in January, Esquire 's 15 Best Winter Books, Paste 's 10 Most Anticipated Nonfiction Books of 2020, and Entertainment Weekly 's 50 Most Anticipated Books of 2020. "A definitive document of a world in transition: I won't be alone in returning to Uncanny Valley for clarity and consolation for many years to come." —Jia Tolentino, author of Trick Mirror: Reflections on Self-Delusion The prescient account of a journey in Silicon Valley: a defining memoir of our digital age. In her mid-twenties, at the height of tech industry idealism, Anna Wiener—stuck, broke, and looking for meaning in her work, like any good millennial—left a job in book publishing for the promise of the new digital economy. She moved from New York to San Francisco, where she landed at a big-data startup in the heart of the Silicon Valley bubble: a world of surreal extravagance, dubious success, and fresh-faced entrepreneurs hell-bent on domination, glory, and, of course, progress . Anna arrived amidst a massive cultural shift, as the tech industry rapidly transformed into a locus of wealth and power rivaling Wall Street. But amid the company ski vacations and in-office speakeasies, boyish camaraderie and ride-or-die corporate fealty, a new Silicon Valley began to emerge: one in far over its head, one that enriched itself at the expense of the idyllic future it claimed to be building. Part coming-age-story, part portrait of an already-bygone era, Anna Wiener's memoir is a rare first-person glimpse into high-flying, reckless startup culture at a time of unchecked ambition, unregulated surveillance, wild fortune, and accelerating political power. With wit, candor, and heart, Anna deftly charts the tech industry's shift from self-appointed world savior to democracy-endangering liability, alongside a personal narrative of aspiration, ambivalence, and disillusionment. Unsparing and incisive, Uncanny Valley is a cautionary tale, and a revelatory interrogation of a world reckoning with consequences its unwitting designers are only beginning to understand. A Macmillan Audio production from MCD